Idiopathic focal epilepsies: the "lost tribe"th. Issue 3 (9th September 2016) - Pal, Deb K.; Ferrie, Colin; Addis, Laura; Akiyama, Tomoyuki; Capovilla, Giuseppe; Caraballo, Roberto; de Saint‐Martin, Anne; Fejerman, Natalio; Guerrini, Renzo; Hamandi, Khalid; Helbig, Ingo; Ioannides, Andreas A.; et al.
Abstract: The term idiopathic focal epilepsies of childhood (IFE) is not formally recognised by the ILAE in its 2010 revision (Berg et al ., 2010 ), nor are its members and boundaries precisely delineated. The IFEs are amongst the most commonly encountered epilepsy syndromes affecting children. They are fascinating disorders that hold many "treats" for both clinicians and researchers. For example, the IFEs pose many of the most interesting questions central to epileptology: how are functional brain networks involved in the manifestation of epilepsy? What are the shared mechanisms of comorbidity between epilepsy and neurodevelopmental disorders? How do focal EEG discharges impact cognitive functioning? What explains the age‐related expression of these syndromes? Why are EEG discharges and seizures so tightly locked to slow‐wave sleep? In the last few decades, the clinical symptomatology and the respective courses of many IFEs have been described, although they are still not widely appreciated beyond the specialist community. Most neurologists would recognise the core syndromes of IFE to comprise: benign epilepsy of childhood with centro‐temporal spikes or Rolandic epilepsy (BECTS/RE); Panayiotopoulos syndrome; and the idiopathic occipital epilepsies (Gastaut and photosensitive types). The Landau‐Kleffner syndrome and the related (idiopathic) epilepsy with continuous spikes and waves in sleep (CSWS or ESES) are also often included, both as a consequence of the shared morphology of the interictal discharges and their potential evolution from core syndromes, for example, CSWS from BECTS. Atypical benign focal epilepsy of childhood also has shared electro‐clinical features warranting inclusion. In addition, a number of less well‐defined syndromes of IFE have been proposed, including benign childhood seizures with affective symptoms, benign childhood epilepsy with parietal spikes, benign childhood seizures with frontal or midline spikes, and benign focal seizures of adolescence. The term "benign" is often used in connection with the IFEs and is increasingly being challenged. Certainly most of these disorders are not associated with the devastating cognitive and behavioural problems seen with early childhood epileptic encephalopathies, such as West or Dravet syndromes. However, it is clear that specific, and sometimes persistent, neuropsychological deficits in attention, language and literacy accompany many of the IFEs that, when multiplied by the large numbers affected, make up a significant public health problem. Understanding the nature, distribution, evolution, risk and management of these is an important area of current research. A corollary to such questions regarding comorbidities is the role of focal interictal spikes and their enduring impact on cognitive functioning. What explains the paradox that epilepsies characterised by abundant interictal epileptiform abnormalities are often associated with very few clinical seizures? This is an exciting area in both clinical and experimental arenas and will eventually have important implications for clinical management of the whole child, taking into account not just seizures, but also adaptive functioning and quality of life. For several decades, we have accepted an evidence‐free approach to using or not using antiepileptic drugs in IFEs. There is huge international variation and only a handful of studies examining neurocognitive outcomes. Clearly, this is a situation ready for an overhaul in practice. Fundamental to understanding treatment is knowledge of aetiology. In recent years, there have been several significant discoveries in IFEs from studies of copy number variation, exome sequencing, and linkage that prompt reconsideration of the "unknown cause" classification and strongly suggest a genetic aetiology. The IFE are strongly age‐related, both with regards to age of seizure onset and remission. Does this time window solely relate to a similar age‐related gene expression, or are there epigenetic factors involved that might also explain low observed twin concordance? The genetic (and epigenetic) models for different IFEs, their comorbidities, and their similarities to other neurodevelopmental disorders deserve investigation in the coming years. In so doing, we will probably learn much about normal brain functioning. This is because these disorders, perhaps more than any other human brain disease, are disorders of functional brain systems (even though these functional networks may not yet be fully defined). In June 2012, an international group of clinical and basic science researchers met in London under the auspices of the Waterloo Foundation to discuss and debate these issues in relation to IFEs. This Waterloo Foundation Symposium on the Idiopathic Focal Epilepsies: Phenotype to Genotype witnessed presentations that explored the clinical phenomenology, phenotypes and endophenotypes, and genetic approaches to investigation of these disorders. In parallel, the impact of these epilepsies on children and their families was reviewed. The papers in this supplement are based upon these presentations. They represent an updated state‐of‐the‐art thinking on the topics explored. The symposium led to the formation of international working groups under the umbrella of "Luke's Idiopathic Focal Epilepsy Project" to investigate various aspects of the idiopathic focal epilepsies including: semiology and classification, genetics, cognition, sleep, high‐frequency oscillations, and parental resources (seewww.childhood-epilepsy.org ). The next sponsored international workshop, in June 2014, was on randomised controlled trials in IFEs and overnight learning outcome measures.